Assam Development Report - (:unkn) unknown (Planning Commission, 2002)
We thank Planning Commission and the Government of Assam for entrusting the task to prepare this report to Indira Gandhi Institute of Development Research (IGIDR). We are particularly indebted to Dr. K. Venkatasubramanian, Member, Planning Commission and Chairman of the Core Committee overseeing the preparation of the Report for his personal interest in this project and encouragement and many constructive suggestions. We are extremely grateful to Dr. Rajan Katoch of the Planning Commission for his useful advice, overall guidance and active coordination of the project, which has enabled us to bring this exercise to fruition. We also thank Ms. Somi Tandon, who helped initiate the preparation of the Report, all the members of the Core Committee and officers of the State Plans Division of the Planning Commission for their support from time to time.
Planning Commission Government of India
Planning Commission Government of India